2019
DOI: 10.1093/emph/eoz014
|View full text |Cite
|
Sign up to set email alerts
|

Gene-drive-mediated extinction is thwarted by population structure and evolution of sib mating

Abstract: Background and objectives Genetic engineering combined with CRISPR technology has developed to the point that gene drives can, in theory, be engineered to cause extinction in countless species. Success of extinction programs now rests on the possibility of resistance evolution, which is largely unknown. Depending on the gene-drive technology, resistance may take many forms, from mutations in the nuclease target sequence (e.g. for CRISPR) to specific types of non-random population structures t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 33 publications
5
95
0
Order By: Relevance
“…Outcomes consistent with chasing behavior have already been observed in other models of suppression gene drives in structured populations 22,24,26 . In these studies, it was generally suggested that the drive efficiency should be high enough to avoid drive loss due to drift but should not be so high that the drive eliminates patches of wild-type and itself before being able to spread to an adjacent region.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Outcomes consistent with chasing behavior have already been observed in other models of suppression gene drives in structured populations 22,24,26 . In these studies, it was generally suggested that the drive efficiency should be high enough to avoid drive loss due to drift but should not be so high that the drive eliminates patches of wild-type and itself before being able to spread to an adjacent region.…”
Section: Discussionsupporting
confidence: 80%
“…Evolution of an increased tendency for inbreeding has been suggested as a mechanism by which populations could avoid the suppressive effects of a gene drive 26 , and our studies in continuous space support this notion. We found that higher levels of inbreeding can indeed substantially reduce the effectiveness of the drive by increasing the likelihood of chasing.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Fusarium graminearum is a homothallic fungus, meaning that it undergoes selfing and outcrossing. In nature, both modes of reproduction are known to occur (Goswami & Kistler, 2004;Trail, 2009), and while outcrossing promotes spread, selfing could potentially limit the drive's spread in populations (Bull et al, 2019). To test if drive could also be observed under random mating in F. graminearum, we crossed the drive and tester strains and monitored resulting genotypes in randomly mating populations (i.e.…”
Section: Selfing Is Not Necessarily An Impediment To Drive Spreadmentioning
confidence: 99%